Mechanisms of telomere maintenance in pediatric brain tumors: Promising targets for therapy – A narrative review - Simone Minasi; Francesca Gianno; Hiba Alzoubi; Manila Antonelli; Felice Giangaspero; Francesca Romana Buttarelli (Glioma, 2020)
Recent advances in genetic and molecular characterization of telomere maintenance mechanisms (TMMs) highlighted their strong relationship with cancer pathogenesis; neoplastic cells rely on two mechanisms to maintain telomere length and escape from replicative senescence: (a) reactivation of telomerase expression and (b) activation of alternative lengthening of telomere (ALT). Our aims are to describe the role of telomere maintenance in the context of recently published literature regarding pediatric brain cancers and to discuss the emerging therapeutic strategies to target telomerase-positive and ALT-positive tumors. In this review, we illustrate the incidence of TMM via telomerase or ALT and discuss the importance of analyzing telomere length and ALT-associated genetic alterations in certain histological/molecular subtypes of pediatric brain tumors, as potential therapeutic biomarkers. Telomerase-dependent TMM is a common mechanism in SHH-medulloblastomas and ependymomas, which could potentially benefit from antitelomerase therapies, while ALT-dependent TMM is more frequently activated in α-thalassemia/mental retardation syndrome X-linked/H3.3-mutated pediatric high-grade gliomas, metastatic medulloblastomas, and choroid plexus tumors, which could potentially be treated with ALT-targeted drugs. Conversely, pediatric low-grade gliomas lack both mechanisms of telomere maintenance, and anti-TMM therapies do not appear to be a promising strategy for these tumors.